Analysis of Equivalence and Non-equivalence in Harry Potter and the Order of Phoenix Novel and its Translation into Indonesian - Saswati, Risna (SCOPE: Journal of English Language Teaching, 2024)
The study sheds light on the translation of non-equivalency at the word level, above the word level, grammatical equivalency, textual equivalency and pragmatic equivalency. The study applied qualitative research in which the data are taken from the novel Harry Potter and the Order of Phoenix. This study uses the theory of equivalence and strategies from Baker (2018). The result reveals that the use of Google translation as machine translation is not recommended for the translator since the translator needs to restructure the translation. Additionally, it is found that Google Translate applies the strategy of literal translation to all levels: the word level, above the word level, the textual level and the pragmatic level.